A dose-dependent relationship between copper burden in female urchin gonads and developmental impairment of their offspring. (May 2018) - Phillips, Nicole E.; Rouchon, Agnes M.
Abstract: We examined transgenerational effects of exposure to copper on early development of offspring in the urchin Evechinus chloroticus, and whether parental exposure mediated offspring response to a further low level exposure to copper during early development. Month-long exposure to elevated copper (25 μgL −1 ) in the laboratory increased copper in gonads of both males and females and reduced gonad size by almost half. There was a negative relationship between adult size and copper burden. Normal larval development and larval size four days after fertilization were both strongly, negatively related to the amount of copper in female gonads in a dose-dependent manner, but fertilization success was unaffected. This demonstrates a transgenerational effect of maternal exposure to copper pollution on offspring performance that is mediated by individual traits of females, but no evidence of strong paternal effects, nor of a low level of copper in the water in which early development occurs. Highlights: Month-long exposure increased copper in gonads of sea urchins and reduced gonad size. There was a negative relationship between adult size and copper burden. Early larval development was negatively related to the copper in female gonads.